Indigenous Australian laws of war: Makarrata, milwerangel and junkarti. (August 2020) - White, Samuel; Kerkhove, Ray
Abstract: Studies in Australian history have lamentably neglected the military traditions of First Australians prior to European contact. This is due largely to a combination of academic and social bigotry, and loss of Indigenous knowledge after settlement. Thankfully, the situation is beginning to change, in no small part due to the growing literature surrounding the Frontier Wars of Australia. All aspects of Indigenous customs and norms are now beginning to receive a balanced analysis. Yet, very little has ever been written on the laws, customs and norms that regulated Indigenous Australian collective armed conflicts. This paper, co-written by a military legal practitioner and an ethno-historian, uses early accounts to reconstruct ten laws of war evidently recognized across much of pre-settlement Australia. The study is a preliminary one, aiming to stimulate further research and debate in this neglected field, which has only recently been explored in international relations.